“This Ambitious Polish Jew”: Rethinking the Conversion and Career of Bishop Isaac Hellmuth - Halpern, Monda (Ontario History, 2007)
Bishop Isaac Hellmuth is the undisputed father of The University of Western Ontario, and his devotion to Christianity is celebrated as part of its rich history. Hellmuth, however, was born a Jew. Both Anglican and evangelical sources have treated his Judaism and his 1841 conversion to Christianity in a variety of ways, but they are limited. This paper will revisit Hellmuth’s conversion and career through a Jewish lens, profiling a Christian missionary movement in which Hellmuth was active as both a prospective apostate and long-time emissary. Hellmuth’s conversion has been described as an exclusively religious experience, but amidst European anti-Semitism, it might have been partly motivated by a desire for position and wealth. Certainly, Hellmuth’s conversion reaped him rewards, although in London, Ontario, he was never quite able to elude his Jewish past.